Active turbidity monitoring during dredged material placement at dredged Hole #86, Atlantic City, New Jersey - Daniel A. Barone; Robert J. Miskewitz; W. Scott Douglas (Environmental Challenges, 2025)
This study presents findings from turbidity monitoring conducted during the open-water hydraulic placement of dredged material at Dredged Hole #86 (DH86), located in the back-bay waterways adjacent to Atlantic City, New Jersey. Turbidity, depth and current measurements were collected using in-situ and manual sensors. Results indicated that the hydraulic dredged material placement operations did not lead to observable increases in turbidity levels above background levels (prior to fill operations). This study demonstrated that placement of dredged material into a subaqueous pit resulted in elevated turbidity, however, the impact was temporary and localized and therefore does not pose a risk to the water quality in the area surrounding the discharge location. DH86 will continue to be a viable placement site for ongoing navigational channel dredging needs in this area, while at the same time providing needed habitat restoration in the back bays of New Jersey. The larger implication is that the project will increase acceptance of dredged material placement into dredged holes as a financially and environmentally responsible method for placement of dredged sediments to perform habitat restoration. There are over 100 dredged holes in New Jersey that can be a sediment sink for the New Jersey Marine Transportation System’s navigation channels.